Humanize nature in the poetry of childhood in Iraq (2003-2015) (Journal of the College of Education for Women, 2019)
That the nature of an important role in children's lives, Including offer them fun and freedom of thinking and capacity in the imagination. And its effective role of poets in general and especially apoet of childhood Selecting from diverse elements, And the rise to the level of human nature In order to enrich the child's imagination And the delivery of various ideas and information in a surprising. And are far from the decision-making and direct screed.this importance we set off For the study of poetic texts for children in Iraq During the research stage. Those texts in which the humanization began clearly,and our offer to these texts in style of detail and precision Not without expressing an my opinion during the research We finished the study conclusion our offer where the most important results that we have And margins According to sources And references on which we based in study